2021
DOI: 10.3390/plants10112395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Siliceous Natural Nanomaterials Applied in Combination with Foliar Fertilizers on Physiology, Yield and Fruit Quality of the Apricot and Peach Trees

Abstract: Siliceous natural nanomaterials (SNNMs), i.e., diatomaceous earth and natural zeolites, have a nanoporous structure with large active surfaces that adsorb cations or polarized molecules. Such nanoporous feature determines the effects related to SNNM utilization as low-risk plant protectants and soil improvers. This work used SNNMs from Romanian quarries as carriers for foliar fertilizers applied to stone-fruit trees, apricot and peach. We determined the effects of SNNMs on the physiology, yield and fruit quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
(107 reference statements)
1
5
0
1
Order By: Relevance
“…Additionally, it also improved the fruit content from total sugar content and TSS percentage, while it minimized the fruit acidity comparing with control in the two seasons. Our results also in the same trend with the findings of Moale et al (2021); they reported that the application of zeolite on apricot and peach increased the yield, fruit quality, and water use efficiency up to 30%.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, it also improved the fruit content from total sugar content and TSS percentage, while it minimized the fruit acidity comparing with control in the two seasons. Our results also in the same trend with the findings of Moale et al (2021); they reported that the application of zeolite on apricot and peach increased the yield, fruit quality, and water use efficiency up to 30%.…”
Section: Discussionsupporting
confidence: 91%
“…The following materials were used for the preparation of the veterinary supplement: oregano essential oil (Solaris, Bucharest, Romania); diatomaceous earth (Sibiciu de Sus quarry, Industriile de Diatomit, Pătârlagele, Buzău, Romania); soy protein isolate (Supro ® Ex 37 HG IO, Solae, Geneva, Switzerland); whey protein concentrate (WPC 80, Milkiland, Warsaw, Poland), calcium hydroxide, Ca(OH) 2 , and potassium hydroxide (KOH) (Chimopar, Bucharest, Romania). The diatomaceous earth was activated by acid leaching and neutralization, with a specific surface area determined using the Brunauer-Emmett-Teller (BET) method of 32.3 ± 1.8 m 2 /g [13]. Aflatoxin B 1 standard, porcine gastric pepsin (400 U mg −1 ), and sodium chloride were supplied by Sigma-Aldrich (Merck Group, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…De forma similar, Oro et al (2020) reportaron que el uso de bioestimulantes con fertilización previa, produjeron mayor cantidad de frutos sanos en cacao, en comparación a tratamientos que solo recibieron aplicación de bioestimulantes sin fertilización. Finalmente, el efecto de la tierra de diatomeas sobre los resultados obtenidos en cacao, pueden deberse a los efectos descritos por Constantinescu et al (2020) y Moale et al (2021), quienes describieron que la aplicación foliar de tierra de diatomeas forma una película en el tejido foliar, que contribuye a reducir la temperatura foliar, aumenta el uso eficiente del agua, mejora la absorción de fertilizantes por la hoja, y que el rendimiento aumenta hasta un 8,1 % con la utilización de tierra de diatomeas con fertilizantes foliares, en comparación con la aplicación de fertilizantes foliares solos.…”
Section: Tratamientosunclassified